Relative shortening and functional tethering of spinal cord in adolescent scoliosis – Result of asynchronous neuro-osseous growth, summary of an electronic focus group debate of the IBSE - Chu, Winnie CW; Lam, Wynnie MW; Ng, Bobby KW; Tze-ping, Lam; Lee, Kwong-man; Guo, Xia; Cheng, Jack CY; Burwell, R Geoffrey; Dangerfield, Peter H; Jaspan, Tim (Scoliosis, 2008)
There is no generally accepted scientific theory for the causes of adolescent idiopathic scoliosis (AIS). As part of its mission to widen understanding of scoliosis etiology, the International Federated Body on Scoliosis Etiology (IBSE) introduced the electronic focus group (EFG) as a means of increasing debate on knowledge of important topics. This has been designated as an on-line Delphi discussion. The Statement for this debate was written by Dr WCW Chu and colleagues who examine the spinal cord to vertebral growth interaction during adolescence in scoliosis. Using the multi-planar reconstruction technique of magnetic resonance imaging they investigated the relative length of spinal cord to vertebral column including ratios in 28 girls with AIS (mainly thoracic or double major curves) and 14 age-matched normal girls. Also evaluated were cerebellar tonsillar position, somatosensory evoked potentials (SSEPs), and clinical neurological examination. In severe AIS compared with normal controls, the vertebral column is significantly longer without detectable spinal cord lengthening. They speculate that anterior spinal column overgrowth relative to a normal length spinal cord exerts a stretching tethering force between the two ends, cranially and caudally leading to the initiation and progression of thoracic AIS. They support and develop the Roth-Porter concept of uncoupled neuro-osseous growth in the pathogenesis of AIS which now they prefer to term ' asynchronous neuro-osseous growth' . Morphological evidence about the curve apex suggests that the spinal cord is also affected, and a 'double pathology' is suggested. AIS is viewed as a disorder with a wide spectrum and a common neuroanatomical abnormality namely, a spinal cord of normal length but short relative to an abnormally lengthened anterior vertebral column. Neuroanatomical changes and/or abnormal neural function may be expressed only in severe cases. This asynchronous neuro-osseous growth concept is regarded as one component of a larger concept. The other component relates to the brain and cranium of AIS subjects because abnormalities have been found in brain (infratentorial and supratentorial) and skull (vault and base). The possible relevance of systemic melatonin-signaling pathway dysfunction, platelet calmodulin levels and putative vertebral vascular biology to the asynchronous neuro-osseous growth concept is discussed. A biomechanical model to test the spinal component of the concept is in hand. There is no published research on the biomechanical properties of the spinal cord for scoliosis specimens. Such research on normal spinal cords includes movements (kinematics), stress-strain responses to uniaxial loading, and anterior forces created by the stretched cord in forward flexion that may alter sagittal spinal shape during adolescent growth. The asynchronous neuro-osseous growth concept for the spine evokes controversy. Dr Chu and colleagues respond to five other concepts of pathogenesis for AIS and suggest that relative anterior spinal overgrowth and biomechanical growth modulation may also contribute to AIS pathogenesis.